Wave climate analysis and determination of sediment diameter for beach fill along the coastline of Luna, La Union - Bolanos, Jan Irene A.; Camelo, Jeane B.; Villalba, Imee Bren O. (Quezon City College of Engineering, University of the Philippines Diliman, 2016)
Wave climate analysis, the study of the condition of waves in a location, is done along the 3-km stretch of coastline along Brgy. Victoria, Luna, La Union using REFDIF1, a wave simulation program. The program shows the wave height distribution as well as wave patterns for the 3km x 3km grid. Wave hindcasting is done through manual computations to acquire the significant wave height and period in deep water. Simulation in prevailing and extreme wave conditions is done. The results are then analyzed to compute for the minimum sediment diameter for the beach fill. The computations yield a 4.5 cm minimum sediment dianleter that prevents the movement of sediments along the shore.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Coast changes -- Philippines -- La Union; Ocean waves; Wave climate analysis